SOFTWARE DEVELOPMENT OF THE PRESSURE ULCER SCALE FOR HEALING (PUSH): AN INNOVATION STUDY - Feitosa, Maria Elisiane Esmeraldo; Leite Sampaio, Luis Rafael; De Oliveira, Joseph Dimas; Soares Feitosa, Yterfania (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To develop a software for pressure injury assessment and monitoring using the pressure ulcer scale for healing (PUSH). Method: This is a methodological research of technological innovation and software development. An application was developed to monitor pressure injuries using the PUSH created by National Pressure Ulcer Advisory Panel, and it went through the content validation process. Result: This study resulted in the first stage of an integrative review, in which nine articles were identified between the years 2012 and 2018. In the second stage, the process of building the application took place. It has 16 screens, among them PUSH scale, monitoring through graphics, and anamnesis. In the third stage, the content validation process was carried out, and it was obtained an overall content validity index of 0.95, an acceptable value to validate an instrument. Conclusion: It was observed that the software is applicable and serves as support to the clinical practice of the nursing professional.